Hybrid single‐carrier‐based pulse width modulation scheme for single‐phase three‐level neutral‐point‐clamped grid‐side converters in electric railway traction. Issue 13 (1st October 2016) - Wang, Shunliang; Song, Wensheng; Zhao, Junhui; Feng, Xiaoyun
Abstract : AC traction power‐supply systems are vulnerable to the high‐order harmonics from grid‐side rectifiers, which are usually single‐phase three‐level neutral‐point‐clamped (NPC) converters. In this study, a dipolar single‐carrier‐based pulse width modulation (SCBPWM) scheme is first designed for the adopted NPC converter. Then, on the basis of the dipolar SCBPWM scheme, a novel hybrid SCBPWM scheme with both unipolar and dipolar modulation modes is proposed to improve high‐order harmonics and mitigate harmonic resonance. In addition, the voltage‐balancing task of the DC‐link capacitors of the NPC converter can be performed by fine adjustment of the separation coefficient in the hybrid SCBPWM. The salient features of the proposed scheme, as compared with the traditional unipolar double‐carrier‐based pulse width modulation, include: (1) lowered high‐order harmonics and total harmonic distortion of the line current; (2) only one carrier signal needed; and (3) voltage fluctuation suppression of the neutral point. Performance of the proposed hybrid SCBPWM scheme for the NPC converter is verified by experimental results.